Predictive Value for Galectin 3 and Cardiotrophin 1 in Hemodialysis Patients. (October 2016) - Hogas, Simona; Schiller, Adalbert; Voroneanu, Luminita; Constantinescu, Daniela; Timar, Romulus; Cianga, Petru; Siriopol, Dimitrie; Bob, Flaviu; Cianga, Corina; Onofriescu, Mihai; Gadalean, Florica; Hogas, Mihai; et al.
Patients with end-stage renal disease (ESRD) have an increased risk of all-cause mortality. The prognostic value of the new cardiac biomarkers, cardiotrophin 1 (CT-1) and galectin 3 (GAL-3), has not yet been defined in hemodialysis (HD) patients. The aim of this study was to determine the use of these novel biomarkers for predicting mortality in HD patients. Plasma GAL-3 and CT-1 concentrations were determined (at baseline) in 88 HD patients followed for 22.2 ± 4.7 months. During the follow-up period, 21 (23.9%) deaths were recorded. According to Cox analysis, the cutoff point for GAL-3 as a predictor of mortality was 23.73 ng/mL, while the cutoff point for CT-1 as a predictor of mortality was 36 pg/mL. In univariate analysis, only GAL-3 >23.73 ng/mL was an independent predictor of mortality (hazard ratio 2.60; 95% confidence interval, 1.09-6.18). In a multivariable Cox proportional hazards model, GAL-3 levels above the cutoff value remained an independent predictor of all-cause mortality. Our data suggest that similar to the general population, GAL-3 is an independent predictor of mortality in HD patients.